Development and validation of a scale for assessing nurses’ approaches to ethical issues - Ebru Çalişkan; Nazike Duruk (BMC Nursing)
Abstract Background A review of the literature indicates that while nurses are aware of ethical issues, they encounter significant challenges in ethical decision-making and its practical implementation. This study aims to develop the “Scale for Assessing Nurses’ Approaches to Ethical Issues (SANAEI)” to evaluate nurses’ approaches to ethical dilemmas in their practice. Methods This study was conducted in two phases using qualitative and descriptive approaches, focusing on nurses working in hospitals in a province of Türkiye. The first phase, aimed at developing the item pool, took place between January 10 and February 24, 2023, with 34 participants. The second phase, conducted from June 3 to October 6, 2024, involved 600 participants, with 300 assigned to Exploratory Factor Analysis (EFA) and 300 to Confirmatory Factor Analysis (CFA). Qualitative data were collected through an “Interview Form”, while quantitative data were obtained using the “Draft Scale Form for Assessing Nurses’ Approaches to Ethical Issues”. Data analysis was performed using MAXQDA for qualitative data and SPSS 25 for quantitative data. Results The initial 78-item pool, derived from qualitative research, underwent content validity analysis, reducing it to 43 items. A pilot study with 50 participants further reduced the item count to 28. EFA resulted in a final 23-item scale with a three-factor structure and factor loadings ranging from 0.459 to 0.846. The three factors explained 56.734% of the total variance. The overall Cronbach’s alpha coefficient was 0.924. The model fit indices were as follows: χ²/df = 3.543, RMSEA = 0.092, and CFI = 0.94. Conclusion The “Scale for Assessing Nurses’ Approaches to Ethical Issues” was determined to be a valid and reliable measurement instrument.